Experimental uremia affects hypothalamic amino acid neurotransmitter milieu - Schaefer, Franz; Vogel, Marcel; Kerkhoffs, Guido; Woitzik, Johannes; Daschner, Markus; Mehls, Otto (Journal of the American Society of Nephrology, 2001)
Abstract. Chronic renal failure is associated with delayed puberty and hypogonadism. To investigate the mechanisms subserving the reported reduced pulsatile release of gonadotropin-releasing hormone (GnRH) in chronic renal failure, this study examined the amino acid neurotransmitter milieu in the medial preoptic area (MPOA), the hypothalamic region where the GnRH-secreting neurons reside, in 5/6-nephrectomized male rats and in ad libitum-fed or pair-fed controls. All rats were castrated and received either a testosterone or a vehicle implant to evaluate additional effects of the prevailing sex steroid milieu. Local excitatory (essential amino acids: aspartate, glutamate) and inhibitory (γ-aminobutyric acid [GABA], taurine) amino acid transmitter outflow in the MPOA was measured by microdialysis via stereotactically implanted cannulae in the awake, freely moving rats. In addition to basal extracellular concentrations, the neurosecretory capacity was assessed by the addition of 100 mM KCl to the dialysis fluid. The mechanisms of neurosecretion were evaluated further by inhibition of vesicular release with the use of Ca2+-free, Mg2+-enriched dialysis fluid and by local perfusion with inhibitors of voltage-dependent synaptic release (1 μM tetrodotoxin) and of GABA reuptake (0.5 mM nipecotic acid). In the uremic rats, basal outflow of GABA, glutamate and aspartate, and K+-stimulated aspartate outflow were increased. K+-stimulated GABA and glutamate release was less sensitive to Ca2+ depletion in the uremic than in the control rats. The elevated basal GABA and essential amino acid outflow in the uremic rats was due to a voltage- and Ca2+-independent mechanism. GABA reuptake was inhibited proportionately by nipecotic acid in uremic and pair-fed control rats. Testosterone supplementation had no independent effects on neurotransmitter outflow. In summary, the amino acid neurotransmitter milieu is altered in the MPOA of uremic rats by a nonsynaptic, nonvesicular mechanism. These abnormalities may contribute to the impaired function of the GnRH pulse generator.